(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article investigates the role of “The Ukrainian language historical grammar” in future philologist training, gives the analysis of historical processes, first of all phonetic that promote better mastering of program material, especially when studying historical alternation and simplification in groups of consonants.